Deconstructing Chronic Low Back Pain in the Older Adult–Step by Step Evidence and Expert‐Based Recommendations for Evaluation and Treatment: Part II: Myofascial Pain. Issue 7 (18th June 2015) - Lisi, Anthony J.; Breuer, Paula; Gallagher, Rollin M.; Rodriguez, Eric; Rossi, Michelle I.; Schmader, Kenneth; Scholten, Joel D.; Weiner, Debra K.
Abstract: Objective: To present an algorithm of sequential treatment options for managing myofascial pain (MP) in older adults, along with a representative clinical case. Methods: A modified Delphi process was used to synthesize evidence‐based recommendations. A multidisciplinary expert panel developed the algorithm, which was subsequently refined through an iterative process of input from a primary care physician panel. Results: We present an algorithm and supportive materials to help guide the care of older adults with MP, an important contributor to chronic low back pain (CLBP). Addressing any perpetuating factors should be the first step of managing MP. Patients should be educated on self‐care approaches, home exercise, and the use of safe analgesics when indicated. Trigger point deactivation can be accomplished by manual therapy, injection therapy, dry needling, and/or acupuncture. Conclusions: The algorithm presented gives a structured approach to guide primary care providers in planning treatment for patients with MP as a contributor to CLBP.